Counter Ions Determine Self-Assembled Nanostructure and Activation Energy of Ion-Conductive Mesogens - Rim, Minwoo; Kim, Woojin; Kang, Dong-Gue; Pham, Huu Huan; Wi, Youngjae; Oh, Mintaek; Ko, Hyeyoon; De Sio, Luciano; Kim, Dae-Yoon; Jeong, Kwang-Un (Wiley - V C H Verlag GmbbH & Co., 2025)
By varying counter ions of ion-conductive mesogens (ICMs) from bromide (Br), to tetrafluoroborate (BF4), and to bis(trifluoromethanesulfonyl)imide (TFSI), the ionic conductivity of ICM is systematically investigated based on their self-assembled nanostructure and activation energy. Thermal and phase transition behaviors of ICM-Br, -BF4, and -TFSI exhibit significant variation based on the anion type. These differences are further reflected in the self-assembled nanostructures of the ICMs, which are characterized through X-ray and electron diffraction experiments. Ionic conductivity measured by electrochemical impedance spectroscopy and activation energy calculated by Arrhenius equation allow us to build the relationship between self-assembled nanostructures of ICMs and their activation energy. The constructed relationship between self-assembled nanostructures and activation energy can provide valuable insights for the development of novel ion-conductive materials.